P170 Risk factors for Mycoplasma genitalium infection in symptomatic males, females and men who have sex with men from three clinical settings in London. (30th June 2016) - Broad, Claire; Harding-Esch, Emma; Harrison, Mark; Soares, Clare; Fuller, Sebastian; Okala, Sandra; Saunders, John; Barber, Tristan; Hay, Phillip; Sadiq, Tariq
Abstract : Background/introduction: Mycoplasma genitalium (MG), a sexually transmitted infection (STI), is increasingly recognised as a cause of major reproductive health sequelae. Treatment has become increasingly difficult due to macrolide and fluoroquinolone antibiotic resistance. MG is not routinely tested for in most UK genitourinary medicine (GUM) clinics, and limited risk-factor data exist for infection in at-risk populations and in different anatomical sites. Aim(s)/objectives: To determine risk factors for MG infection in symptomatic male and female patients accessing three London GUM clinics. Methods: Patients aged ≥16 years, symptomatic of an STI (or Chlamydia, Gonorrhoea, Trichomonas vaginalis, or non-specific urethritis contact) were consented. Additional-to-routine samples provided were vulvovaginal swab (VVS) (females), first void urine (FVU) (men-who-have-sex-with-women (MSW), (men-who-have-sex-with-men (MSM)), pharyngeal and rectal swabs (MSM). Samples were tested using the FTD Urethritis Plus Test kit and positives confirmed by Polymerase Chain Reaction. Risk factors were analysed using univariate and multivariate logistic regression. Results: MG was detected in: 10.7% (95% CI 7.9%–13.5%) patients; 7.9% (95% CI 4.86%–10.94%) VVS; 19.4% (95% CI 11.76%–27.04%) MSW urine; 1.6% (95% CI 0%–4.72%) MSM urine; 0% MSM pharynx; 8.1% (95% CI 1.31%–14.89%) MSM rectum. Discussion/conclusion: MG positivity was highest in MSW compared to the other patient groups, with younger age being the only risk factor for infection, remaining after multivariate analysis. The presence of rectal MG despite a lack of urogenital infection in MSMs warrants further investigation with a larger cohort. Overall the results indicate high MG positivity across symptomatic male and female populations.